JPER Numbers (Journal of Planning Education and Research, 1991)
Background Diagnostic errors are a major concern, particularly when long-standing diagnostic criteria are updated. Following the 2017 World Workshop on the Classification of Periodontal and Peri-implant Diseases and Conditions, a new classification was released in 2018. Subsequently, the dental community initiated steps to teach the updated classification to dental healthcare professionals. This scoping review aimed to identify the different educational approaches used to teach the 2017 periodontal classification. Methods English language articles, published between 2018 and April 2026, reporting on an educational approach to teach the 2017 periodontal classification were searched in MEDLINE, Scopus, Web of Science, and Google Scholar. Results From a total of 1487 articles initially screened, 28 selected articles were subjected to full-text review, and 18 articles were included in this scoping review. The educational approaches used to teach the 2017 periodontal classification were lectures with case-based scenarios, blended learning, team-based learning, flipped classroom, flowcharts, algorithms, calibration sessions, a mobile application, and software applications. These educational approaches were classified into theoretical, applied clinical, and technology-assisted applied clinical approaches. For flowcharts and algorithms, randomized controlled trials have been conducted to validate their educational benefit. Several of the educational approaches were associated with improved diagnostic accuracy among dental healthcare professionals of varying expertise and training. Conclusion Various educational approaches have been used to teach the 2017 periodontal classification, with potential benefits for diagnostic accuracy and trainee confidence. However, further research is needed to better define their impact on periodontal diagnosis and clinical practice. Plain language summary Updating diagnostic systems can lead to errors, which makes effective training important. After a new periodontal disease classification was introduced in 2018, educators developed different ways to teach it to dental health care professionals. This review examined those teaching methods. After searching major databases for English-language studies, 1,487 articles were initially identified and, ultimately, 18 were included in the final review. There was a wide range of methods used to teach the 2017 periodontal classification and included lectures with case scenarios, blended and flipped learning, team-based learning, flowcharts, decision-making algorithms, calibration sessions, and mobile or software applications. Some methods, particularly flowcharts and decision-making algorithms, have been tested in clinical trials and have been shown to improve learning. Overall, several approaches were associated with the improved ability of clinicians to make accurate diagnoses, regardless of their level of experience. These findings suggest that various strategies are available to effectively teach the 2017 periodontal classification, and that they may improve both diagnostic accuracy and learner confidence. However, more research is needed to determine how well these methods translate into better clinical practice.